2018
DOI: 10.1507/endocrj.ej17-0229
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of adenosine monophosphate-activated protein kinase suppresses bone morphogenetic protein-2-induced mineralization of osteoblasts <i>via</i> Smad-independent mechanisms

Abstract: Abstract. Previous studies showed that adenosine monophosphate-activated protein kinase (AMPK), which plays as an intracellular energy sensor, promotes the differentiation and mineralization of osteoblasts via enhancing expression of bone morphogenetic protein (BMP)-2, which is a potent inducer of osteoblastogenesis. Thus, the aim of this study was to examine the roles of AMPK in BMP-2-induced osteoblastogenesis. We used a murine osteoblastic cell line MC3T3-E1 and a murine marrow stromal cell line ST2. BMP-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Combined with the results of this study, SAC affects the expression of Runx2, Osx, and OCN by activating the AMPK/SIRT1 signaling pathway, thereby promoting bone development. 26,27 Therefore, this study suggests that SAC can promote osteogenic differentiation of BMSCs in osteoporotic rats by activating the AMPK/SIRT1 pathway.…”
Section: Discussionmentioning
confidence: 76%
“…Combined with the results of this study, SAC affects the expression of Runx2, Osx, and OCN by activating the AMPK/SIRT1 signaling pathway, thereby promoting bone development. 26,27 Therefore, this study suggests that SAC can promote osteogenic differentiation of BMSCs in osteoporotic rats by activating the AMPK/SIRT1 pathway.…”
Section: Discussionmentioning
confidence: 76%
“…We found that 10 −6 mol/L of BMP2 concentration exhibited optimum stimulation, and FAK was demonstrated to be overexpressed following BMP2-induced osteogenic differentiation. Next, cell proliferation and metabolism were evaluated, and our findings revealed (Takeno, Kanazawa, Notsu, Tanaka, & Sugimoto, 2018). Another study showed that the BMP pathway inhibitor could block the polydatin-induced osteogenesis-potentiating effects through the inhibition of the Wnt/β-catenin pathway in BMSCs (X. J. .…”
Section: Discussionmentioning
confidence: 82%
“…Studies have confirmed that AMPK and Wnt signaling pathways play important roles in BMP‐induced osteogenic differentiation. It has been reported that inhibition of AMPK activation could significantly decrease the expression of OCN, Runx2, and ALP following BMP2‐enhanced mineralization of osteoblasts (Takeno, Kanazawa, Notsu, Tanaka, & Sugimoto, ). Another study showed that the BMP pathway inhibitor could block the polydatin‐induced osteogenesis‐potentiating effects through the inhibition of the Wnt/β‐catenin pathway in BMSCs (X. J. Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, miRNAs are involved in some key processes of PMOP. Studies have shown that by inhibiting adenosine monophosphate-activated protein kinase, the mineralization of osteoblasts induced by bone morphogenetic protein-2 (BMP-2) can be inhibited through the non-Smad mechanism [18] . Adenosine monophosphate-activated protein kinase (AMPK), a serine/threonine kinase, is involved in bone remodelling.…”
Section: Discussionmentioning
confidence: 99%